Benzophenone guttiferone A from Garcinia achachairu Rusby (Clusiaceae) Presents Genotoxic Effects in Different Cells of Mice - Terrazas, Peterson Menezes [UNESP]; Marques, Eduardo de Souza [UNESP]; Bolda Mariano, Luisa Nathalia; Cechinel-Filho, Valdir; Niero, Rivaldo; Andrade, Sergio Faloni; Maistro, Edson Luis [UNESP] (Public Library Science, 2013)
Benzophenones from natural sources and those of synthetic analogues present several reports of potent biological properties, and Guttiferone A represents a promising medicinal natural compound with analgesic and gastroprotective profiles. Considering that there are no reports that assess the genetic toxicity of Guttiferone A, the present study was undertaken to investigate the genotoxic potential of this benzophenone isolated from seeds of Garcinia achachairu in terms of DNA damage in different cells of Swiss albino mice using the comet assay, and its clastogenic/aneugenic effects in bone marrow cells in vivo by the micronucleus test. Cytotoxicity was assessed by scoring polychromatic (PCE) and normochromatic (NCE) erythrocytes ratio. Guttiferone A was administered by oral gavage at doses of 15, 30 and 60 mg/kg. The results showed that Guttiferone A produced genotoxic effects in leukocytes, liver, bone marrow, brain and testicle cells and clastogenic/aneugenic effects in bone marrow erythrocytes of mice. The PCE/NCE ratio indicated no cytotoxicity. Since guttiferone A is harmful to the genetic material we suggest caution in its use by humans.